Comparison of sexual abuse survivors from two different geographical regions of Turkey in terms of the sociodemographic and abuse-related characteristics - (:unkn) unknown (Yerkure Tanitim ve Yayincilik, 2014)
Objective: The aim of this study is to compare the sociodemographic and abuse-related data of the children who have presented to the Antalya and Diyarbakir University hospitals due to sexual abuse. Method: The patient files of 172 children between the ages of 4-17 presented to the Akdeniz University, Department of Child and Adolescent Psychiatric Health and Diseases (CAPHD) Clinic within the year 2010, and of 167 children between the ages of 4-17 presented to the Dicle University CAPHD Clinic during the year 2012 were scanned and the sociodemographic and abuse-related data of the patients were recorded. Results: In the Diyarbakir group, the total years of education of the child, the total years of education of the mother, and the total years of education of the father were significantly lower, while the mean number of the siblings was significantly higher. The number of the male abuse survivors in the Diyarbakir group was significantly higher. The family structure where the parents are alive and living together was significantly more frequent in the Diyarbakir group. No difference in terms of the occurrence of penetration and relationship with the abuser was observed between the groups. Conclusion: Within the framework of this study, the characteristics of the survivors of abuse between two socioculturally, economically and ethnically different regions of Turkey (the Mediterranean region and the south-east Anatolian region) have been investigated. This study has demonstrated that some of the sociodemographic and abuse-related characteristics of sexual abuse in Turkey differs between these regions. We are of the opinion that efforts to prevent sexual abuse should be restructured in the light of these results. For instance, prevention of child labour, increasing the literacy rate of the individuals and promoting family planning efforts in south-east Anatolia should be the primary focus of these efforts.
Keywords: Abuse; Forensic medicine; Incest; Sexual abuse